Reconstruction of Criminal Liability in Infanticide of Children Born out of Wedlock A Juridical Feminism Perspective - Yuni Ristanti; Atika Zahra Nirmala (Rechtsvinding, 2026)
The phenomenon of infanticide involving children born out of wedlock reflects not merely individual conduct but a complex interplay of psychological pressure, social stigma, and gender inequality. This study aims to analyze the regulation of infanticide under the Indonesian Criminal Code, examine the ambiguity of the phrase “fear of being discovered by others,” and assess criminal liability from a feminist legal perspective, including the role of the biological father. This research employs a normative legal method with statutory and conceptual approaches. The findings indicate that Article 460 constitutes a delictum proprium that designates the mother as the offender based on biological conditions. However, its formulation remains partial and fails to address underlying structural factors. The phrase “fear of being discovered by others” is vague and may lead to interpretative disparities. From a feminist legal perspective, the provision reproduces gender inequality by concentrating liability on women, while the role of the biological father remains insufficiently addressed. Accordingly, reconstructing criminal liability to incorporate the role of the biological father and broader social factors is necessary to achieve gender-sensitive substantive justice.